The Potential Utilization of Young Teak Leaves (Tectona grandis Linn.f.) as Basic Ingredients on Producing Anti-cancer Herbal Tea - Nur Ahmad Rudin; Rini Rahmawati; Asma' Hulaimah (Jurnal Pendidikan Biologi Undiksha, 2022)
Gunungkidul Regency is the main teak tree (Tectona grandis Linn.f.) producing area in Special Region of Yogyakarta, Indonesia. Their trunks are commonly used for furniture and buildings, while leaves are still less of use. Teak leaves contain antioxidant compounds in form of flavonoids that play important role in protecting the body against damaging free radicals in cancer sufferers. The number of cancer sufferers in Indonesia is still high, but cancer problem not yet be handled optimally because cannot be fully reached by the community. The aims of this review are studying the production process of herbal tea from young teak leaf and mechanism of flavonoids as an anticancer. This review was conducted by literature study. The writing source is then analyzed and synthesized to draw conclusions. The results obtained production process of young teak leaf herbal tea through several stages, picking, washing, withering, cutting, fermentation, drying, and packaging. The anticancer activity in young teak leaf herbal tea is influenced by the content of flavonoids as antioxidants that can neutralize free radicals and prevent cancer. The conclusion of this review are young teak leaves (T. grandis) can be used as basic ingredient in herbal teas that are good for health, and flavonoids in young teak leaves are antioxidants that potential as anticancer substances.